Examining the relationship between organizational intelligence, religious commitment, spiritual well-being, and organizational agility among multireligious creative economy businessmen in Yogyakarta - Quraisy, Mujahid; Nugroho, Anton Priyo (Universitas Islam Indonesia, 2024)
Introduction Organizational agility, a novel concept in the business domain, measures the speed and flexibility with which organizations can face inevitable disruptions, particularly among creative economy actors with a religious foundation. Objectives This study examines the causal relationship between organizational intelligence, religiosity, spirituality, and organizational agility. Method The study employed a multivariate associative hypothesis testing approach using path analysis to investigate the relationships among organizational agility (OA), organizational Intelligence (OI), religious commitment (RC), and spiritual well-being (SWB). Measurement instruments, including the agility capabilities scale, religious commitment scale, spiritual well-being scale, and organizational intelligence scale, were adapted and validated as psychometric tools within Indonesian society's specific cultural and behavioral context. The sample consisted of 150 creative economy actors involved in religious organizations and engaged in the fashion, culinary, and handicraft sectors. Data analysis was conducted using IBM SPSS Statistics and SmartPLS. Results The findings indicate that religious commitment does not significantly impact organizational agility but positively and significantly influences organizational intelligence. Furthermore, organizational intelligence significantly contributes to organizational agility. However, spiritual well-being does not significantly influence organizational agility or intelligence. Implications These findings have implications for practitioners and decision-makers who want to develop successful business strategies in the religious-based creative economy sector. They emphasize the importance of religious commitment and the enhancement of spiritual values. Originality/Novelty This study contributes to the literature on organizational intelligence, religiosity, spirituality, and organizational agility in creative economy businesses.